Adaptive optics imaging can break the central caustic cusp approach degeneracy in high-magnification microlensing events - Terry, Sean K.; Bennett, David P.; Bhattacharya, Aparna; Koshimoto, Naoki; Beaulieu, Jean-Philippe; Blackman, Joshua W.; Bond, Ian A.; Cole, Andrew A.; Lu, Jessica R.; Marquette, Jean Baptiste; Ranc, Clément; Rektsini, Natalia; et al. (The astronomical journal, 2022)
We report new results for the gravitational microlensing target OGLE-2011-BLG-0950 from adaptive optics images using the Keck Observatory. The original analysis by Choi et al. and reanalysis by Suzuki et al. report degenerate solutions between planetary and stellar binary lens systems. This particular case is the most important type of degeneracy for exoplanet demographics because the distinction between a planetary mass or stellar binary companion has direct consequences for microlensing exoplanet statistics. The 8 and 10 yr baselines allow us to directly measure a relative proper motion of 4.20 ± 0.21 mas yr−1, confirming the detection of the lens star system and ruling out the planetary companion models that predict a ∼4× smaller relative proper motion. The Keck data also rule out the wide stellar binary solution unless one of the components is a stellar remnant. The combination of the lens brightness and close stellar binary light-curve parameters yields primary and secondary star masses of and at a distance of kpc and a projected separation of au. Assuming that the predicted proper motions are measurably different, the high-resolution imaging method described here can be used to disentangle this degeneracy for events observed by the Roman exoplanet microlensing survey using Roman images taken near the beginning or end of the survey.
Gesehen am 18.01.2023